Strengthening environmental, social, and governance accountability in international financial institutions - Azizov, Elman; Azizli, Aytan (Goodwood Publishing, 2025)
Purpose: This study examines how international financial institutions (IFIs) integrate accountability for environmental, social, and governance (ESG) issues into financial governance and decision-making. It assesses whether existing frameworks translate sustainability commitments into binding oversight or primarily function as legitimacy tools in global finance. Methodology/Approach: A qualitative comparative analysis was conducted using policy frameworks, evaluation reports, audit findings, and peer-reviewed research from 2018–2025. Legitimacy theory and principal–agent dynamics guided interpretation, supported by a coding matrix reviewing rule design, monitoring scope, stakeholder engagement, and data verifiability. Results/Findings: Findings show that sustainability standards are increasingly embedded in institutional mandates, but implementation remains uneven. Environmental integration is the most advanced, while social safeguards are limited by resourcing and political constraints. Governance accountability remains restricted by institutional mandates. Digital monitoring tools improve oversight but raise concerns about ethical design and unequal technical capacity. Conclusions: ESG frameworks within IFIs provide strong normative commitments but lack binding enforcement. This creates a persistent gap between institutional ambition and operational practice. Stronger accountability requires harmonized metrics, independent verification, and participatory mechanisms capable of converting transparency into enforceable oversight. Limitations: Limited access to internal deliberations and the lack of longitudinal community-level data constrain assessments of long-term effectiveness. Contribution: The study links normative expectations behind ESG accountability with operational control mechanisms in IFIs. It proposes a reform agenda emphasizing mandatory disclosure, independent oversight bodies, and inclusive monitoring systems—framing ESG accountability as a shift from voluntary transparency to enforceable stewardship in global finance.